Pelatihan Konten Kreator Meningkatkan Kreatifitas Komunitas Disabilitas Mata Hati - Dwi Prasetyo; ryo aldyanto (LPPM Stikosa - AWS, 2023)
This fieldwork study program aims to explore the impact of content creator training on enhancing creativity within the Blind Heart Disability Community. This community consists of individuals with various visual impairments who often face difficulties in expressing themselves and sharing their stories with the outside world. The research methodology involves implementing content creator training that includes theoretical approaches, skill development, and the use of current technology in creative content production. The training participants are members of the Blind Heart Disability Community who have an interest in developing their creative skills. The research findings indicate that content creator training has a significant positive impact on enhancing individual creativity within the community. Participants reported an improvement in their ability to express ideas, tell stories, and produce creative content relevant to their life experiences. They also reported increased self-confidence and social engagement within the community. Additionally, this training enables members of the Blind Heart Disability Community to utilize existing technology to expand the reach and impact of their creative work. By combining theoretical knowledge and technical skills acquired through the training, they are able to create inspiring and positively impactful content for the broader society.This study demonstrates that content creator training can be an effective tool in enhancing the creativity of individuals with visual impairments and strengthening their community. The increased creative skills and social engagement of the participants can bring about positive changes in how they interact with the world and expand their opportunities to create social impact through their creative works.